Terrain characterization of mountanious forest area in Cameron Highland - Ahmad Zawawi, Azita; Lau, Paul; Balakrishnan, Thinaraj (Forestry Department Peninsular Malaysia, 2019)
The paper presents the analysis of terrain parameters based on Digital Terrain Model (DTM) generated in the mountainous forest reserve of Cameron Highland. Terrain analysis was conducted within SAGA GIS using DTM of 10m resolution, where elevation, slope, LS Factor and TW Index were computed. The results indicated that Cameron Highland is described by various terrain characteristics, steep slopes and the forested area can be classified as sensitive. The method applied enables evaluation of forest site stability and productivity based on terrain perspective, which are important to assist forest resource management planning.